The neurochemical aspects of Alzheimer's disease. - Almeida, R (1995)
Alzheimer's disease is one of the most severe and most common progressive neurodegenerative diseases of ageing. It accounts for a significant number of cases of senile dementia. It is a major health problem, considering the current increase in the geriatric population all over the world. The purpose of this article is to review the neurochemical and histopathological aspects of Alzheimer's disease as well as the most recent therapeutical advances in this area.